The Implementation of Management to Improve the Quality of Learning in Islamic Religious Education at the Private Aliyah Madrasah YPIPL Gunung Tua Padang Lawas Utara - Tanjung, Akbar; Zulhamri, Zulhamri; Harahap, Aidul Azhari (Fahmina: Jurnal Pendidikan Islam, 2025)
One of the efforts to improve the quality of Islamic Religious Education is to improve all aspects of education implementation, including management which includes planning, supervision, staffing, and professionalism. This study aims to examine the implementation of PAI learning quality improvement management at MAS YPIPL Gunung Tua Padang Lawas Utara, as well as identify obstacles in its implementation. This research is a descriptive qualitative research using observation, interview, and documentation techniques. The results of the study show that madrasah heads play an important role in the implementation of learning activities, the improvement of work programs, and school activity guidelines. Quality improvement efforts include management, educators, finance, curriculum, learning processes, and facilities and infrastructure. Internal obstacles include a lack of synergy in the implementation of the program, while external obstacles are in the form of low understanding from schools, stakeholders, weak cooperation, and lack of teacher training.